The Effect of Brand Image on Online Purchase Decision with Mediation Word of Mouth on Fashion Products in Denpasar-Bali Province - I.A Pt. Santi Purnamawati; I Made Wianto Putra; Ni Made Wahyuni (Jurnal Ekonomi dan Bisnis Jagaditha, 2022)
The purpose of this study was to develop and test the impact of brand image on online buying decisions through reviews of fashion products in Bali, Indonesia. This study uses a questionnaire method that is systematically conducted based on the purpose of the study. The number of respondents was 100 respondents. This study uses the Likert scale to measure variables when testing validity and reliability variables. This study was analysed by a PLS-based SEM. The results of this study show that (1) brand image has a great influence on electronic word-of-mouth, (2) brand image has a big influence on online purchase decisions, and (3) word-of-mouth has a big influence. Communicate your brand image and online purchase decision with online purchase decision and (4) word of mouth.